2013
DOI: 10.1152/ajpheart.00699.2012
|View full text |Cite
|
Sign up to set email alerts
|

Pressure overload differentially affects respiratory capacity in interfibrillar and subsarcolemmal mitochondria

Abstract: Schwarzer M, Schrepper A, Amorim P, Osterholt M, Doenst T. Pressure overload differentially affects respiratory capacity in interfibrillar and subsarcolemmal mitochondria. Years ago a debate arose as to whether two functionally different mitochondrial subpopulations, subsarcolemmal mitochondria (SSM) and interfibrillar mitochondria (IFM), exist in heart muscle. Nowadays potential differences are often ignored. Presumably, SSM are providing ATP for basic cell function, whereas IFM provide energy for the contrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 55 publications
4
32
0
4
Order By: Relevance
“…Most studies have reported the effects of cardiac hypertrophy associated with VO or pressure overload on subpopulations of mitochondria. It is of interest that interfibrillar mitochondria show a greater respiratory capacity than subsarcolem- mal mitochondria in healthy Spague-Dawley rat hearts but have greater depression of respiratory capacity and LV contractile dysfunction after 20 wk of pressure overload (35). The use of the Seahorse extracellular flux analyzer provides the ability to localize the metabolic changes to intact cardiomyocytes excluding contamination from multiple cells types, maintaining mitochondrial localization in the cell, and obviating damage to mitochondria during isolation (14,16,32).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have reported the effects of cardiac hypertrophy associated with VO or pressure overload on subpopulations of mitochondria. It is of interest that interfibrillar mitochondria show a greater respiratory capacity than subsarcolem- mal mitochondria in healthy Spague-Dawley rat hearts but have greater depression of respiratory capacity and LV contractile dysfunction after 20 wk of pressure overload (35). The use of the Seahorse extracellular flux analyzer provides the ability to localize the metabolic changes to intact cardiomyocytes excluding contamination from multiple cells types, maintaining mitochondrial localization in the cell, and obviating damage to mitochondria during isolation (14,16,32).…”
Section: Discussionmentioning
confidence: 99%
“…These authors reported a reduced capacity for free radical scavenging that was specific for SSM. In contrast, rats that underwent transverse aortic constriction for 20 wk displayed decreased total mitochondrial content, as well as decreased state 3 and state 4 respiration rates, which impacted IFM to a greater extent (115). It is unclear as to why the results differ, but it may be related to the differences in pathological model used and/or animal model of choice.…”
Section: Pathological Influencementioning
confidence: 97%
“…Producción de ATP para los procesos de contracción y relajación [28], [29]. Estructura Redondas con crestas más compactas (lameliformes) [18], [30].…”
Section: Ssm Ifm Funciónunclassified
“…Velocidad de consumo de oxígeno durante la síntesis de ATP Alta (miocardio de perro y humano) [22], [23]. Alta (miocardio de roedores) [21], [31], [32] 4 Disfunción cardíaca asociada a mitocondrias disfuncionales…”
Section: Susceptibilidadunclassified
See 1 more Smart Citation